Multimedia para el proceso - aprendizaje del área de ciencias naturales en los niños de 4to y 5to año de educación básica de la unidad educativa “Juan XIII” del cantón Yantzaza, provincia de Zamora Chinchipe, periodo lectivo 2013 – 2014 - Silva Montaño, Servio Rodrigo (2015)
This thesis work, refers to a study on: MULTIMEDIA FOR THE LEARNING PROCESS OF NATURAL SCIENCES AREA IN CHILDREN OF 4th and 5th YEAR BASIC EDUCATION OF UNIDAD EDUCATIVA "JUAN XIII" CANTON Yantzaza, PROVINCE DE ZAMORA CHINCHIPE, LECTIVE PERIOD 2013 – 2014. Raised the general objective of designing and developing a Multimedia for teaching - learning of the subject of Natural Sciences in children in 4th and 5th Year Basic General Education of School. The methods used for this research were: scientific, descriptive, deductive - inductive, synthetic and statistician which helped to properly route each of the phases of research and conceptualizations respective analyzes; techniques of data collection were the survey applied to Natural Science teachers and children in 4th and 5th year EGB. According to the most outstanding results of the survey of teachers shows that 100% there is a need of software as a technological tool as this will come more easily to the students with the knowledge, they do not only provide the ability to display static text, but present animated images, videos and other to motivate and bring interest for learning in the subject. Also in the surveys done for the children in the school the need for multimedia is note as these 80% say they would like to learn using technological tools such as computer, Internet and mainly the Multimedia. Since well posed multimedia products can expand the field of presentation similar to chains of associations of the human mind forms. The connectivity provided by hypertext makes multimedia programs are not merely static presentations with images and sound, but infinitely varied and informative interactive experience. With the advancement of technology and computing, the personal computers have built new visual, auditory possibilities and capabilities of storing large amounts of information, so that its application has become a necessity in the classroom as a fundamental part between the most important teaching aids in the learning process of human beings.